Mobile Phones: The Intersection of Technology, Policy and Social Issues - Manique, Cooray (2008)
In recent years, we have seen an explosion of mobile phone use, with an estimated 3.3 billion mobile phone subscribers worldwide.(1) Among this number a significant portion of users are children.(2) This is a group that has embraced mobile phone technology more than any other. This obvious appeal of the technology by children could be due to the fact that mobile phones offer privacy, ease of communication, contact with friends and relatives and arguably an exceptionally useful tool that advances personal communication. For instance, the new generation devices are no longer mobile phones only, but have functions which could carry out activities once available only on the Internet. Now, mobile phones offer Third Generation technology, access to a diverse mix of information including, video, camera functions, music, games, Internet browsing, chatting and services such as Short Message Services ("SMS") and Multimedia Message Services, ("MMS") among others. Therefore, every technological advance that provides such dramatic benefits has consequential social costs. It is these consequences of mobile phone usage that warrants more attention especially for the young.